Photon-pair generation using inverse-designed thin-film lithium niobate mode converters - Kwon, Kiwon; Heo, Hyung Jun; Lee, Dongjin; Kim, Hyeongpin; Jang, Hyeong Soon; Shin, Woncheol; Lim, Hyang Tag; Kim, Yong Su; Han, Sang Wook; Kim, Sangin; Shin, Heedeuk; Kwon, Hyounghan; et al. (Conference on Lasers and Electro-Optics/Pacific Rim, CLEO-PR 2024 in Proceedings 2024 Conference on Lasers and Electro-Optics Pacific Rim (CLEO-PR), 2024)
Spontaneous parametric down-conversion is a fundamental technique for producing entangled photon pairs. Here, we employ modal phase matching with straight waveguide instead of the PPLN method and show SPDC efficiency is higher with mode converter.
Keywords: Entangled photon pairs; Lithium niobate; Modal phase matching; Mode converter; Photon pairs generations; Spontaneous parametric down-conversion; Straight waveguides; Thin-films